2021
DOI: 10.3233/nre-201583
|View full text |Cite
|
Sign up to set email alerts
|

Combined cognitive and motor training improves the outcome in the early phase after stroke and prevents a decline of executive functions: A pilot study

Abstract: BACKGROUND: The negative impact of cognitive dysfunction on motor rehabilitation as a relearning-process is well known in stroke patients. However, evidence for combined cognitive and motor training (CMT) is lacking. OBJECTIVE: To evaluate the effects of combined CMT in early stroke rehabilitation. METHODS: In a controlled pilot study, 29 moderately affected stroke patients with low-level motor performance and cognitive impairment received motor therapy plus either cognitive (experimental group, EG) or low-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The range of time since stroke was 6 d to 5 years. Three (11.1%) [ 37 , 40 , 45 ], four, 13, and four articles included the acute (< 1 month), subacute (18.5%) [ 22 , 26 , 30 , 43 , 44 ], chronic (48.1%) [ 24 , 27 29 , 31 34 , 36 , 38 , 39 , 42 , 47 , 48 ], and subacute to chronic (14.8%) phases [ 23 , 25 , 35 , 46 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of time since stroke was 6 d to 5 years. Three (11.1%) [ 37 , 40 , 45 ], four, 13, and four articles included the acute (< 1 month), subacute (18.5%) [ 22 , 26 , 30 , 43 , 44 ], chronic (48.1%) [ 24 , 27 29 , 31 34 , 36 , 38 , 39 , 42 , 47 , 48 ], and subacute to chronic (14.8%) phases [ 23 , 25 , 35 , 46 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions were cognitive rehabilitation (6/27 articles, 22.2%) [ 27 , 35 , 39 , 45 , 47 , 48 ], VR (6/27 articles, 22.2%) [ 23 , 26 , 29 , 31 , 32 , 38 ], NIBS (4/27 articles, 14.8%) [ 25 , 26 , 28 , 40 ], DT training (3/27 articles, 11.1%) [ 22 , 33 , 34 ], and other various training methods (8/27 articles, 29.6%) [ 24 , 30 , 37 , 41 44 , 46 ]. The intervention period was at least twice a week, and the duration varied from 2 weeks to 3 months and was not consistent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that WMT is an effective cognitive rehabilitation strategy in stroke patients for improving individual WM capacity, as well as the performance of untrained WM tasks and tasks that show far-transfer effect (Peers et al, 2020;Eschweiler et al, 2021;Nikravesh et al, 2021). However, the neural effects following WMT in stroke patients remain largely unclear and have been poorly studied.…”
Section: Introductionmentioning
confidence: 99%